PENGARUH VARIASI KONSENTRASI DAN DEBIT PADA PENGOLAHAN AIR ARTIFISIAL (CAMPURAN GREY WATER DAN BLACK WATER) MENGGUNAKAN REAKTOR UASB - Samudro, Ganjar; Syafrudin, Syafrudin; Yazid, Fauzia Rahmiyati (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2012)
In this study Mixture of domestic grey water and black water were investigated. This Mixture consists of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), and  Nitrate  (NO3).  This  research  investigated  the  influence  of  concentration  and  flow  variation parameters  to  treating  the  Mixture  Grey  Water  and  Black  Water.  Effluent  quality  of  decreasing concentration varied by the concentration and flow recorded BOD was about 102-544 mg/l, COD was about 287-1.230 mg/l, TSS was about 280-780 mg/l and for treating  nitrate the result was fair enough than others was about 4-12 mg/l.  According to the flow variation resulted the retention time are 4, 6 and 8 hours. The best effluent quality was happened 878 mg/LCOD, and varied by flow are 0,125. The results  of  research  showed  the  higher  concentration  will  decrease  the  value  of  BOD  and  Nitrate removal, due to the influence of pH.The higher flow will decrease the value of BOD and increase COD, TSS, and Nitrate removal, and  optimum flow condition was 0,125 l/hour.